Emerson as Poet: The Originality of Emerson and Poe in American Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Americans, who achieved political independence, desired of independence in their national culture and literature. The 1820s produced such great writers as Washington Irving, James Penimore Cooper and William Cullen Bryant. Irving and Cooper wrote the best kind of fiction, but it was all modeled upon European literature. So was the case with Bryant, the Poet. But Edgar Allan Poe though from the South, wrote the original kind of poetry, achieving a measure of beauty. Emerson was just his another contemporary from the north, writing the original kind of poetry. He is known for the use of symbolism. Emerson’s originality is as profound as that of Poe, and the theories of the two supplement each other. Poe sought an aesthetic base for poetry Emerson, a moral. Poe explored mainly the possibilities of rhythm Emerson, of symbol. The two together directed the course of American poetry since their time by turning from borrowed conventions.